IS IT BETTER TO STUDY ABROAD OR IN ONE’S HOME COUNTRY? - Ixtiyorova Shahrizoda Qudrat qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Introduction In the context of accelerating globalization and expanding educational mobility, the debate over whether it is more beneficial to study abroad or in one’s home country has become increasingly significant. Higher education today is not merely a means of acquiring knowledge but also a pathway to professional development and global integration. While studying abroad is often associated with intercultural exposure and enhanced career prospects, pursuing education domestically provides financial stability and social continuity. This essay critically examines both perspectives by analyzing their academic, economic, and social implications before arguing that the preferable choice ultimately depends on individual priorities and circumstances. In an era characterized by globalization and increased academic mobility, the question of whether it is better to study abroad or in one’s home country has become highly relevant. While studying abroad offers exposure to new cultures and academic systems, remaining in one’s home country provides stability and affordability. Both options present distinct advantages and challenges, and the optimal choice depends largely on individual goals and circumstances. One of the most compelling arguments in favor of studying abroad is the opportunity for intercultural development. Immersion in a foreign environment enhances linguistic proficiency, adaptability, and global awareness. According to UNESCO (2021), international student mobility promotes intercultural dialogue and fosters mutual understanding among nations. Students who study abroad often develop independence, resilience, and cross-cultural communication skills—competencies that are increasingly valued in the global labor market.